PERBANDINGAN NILAI TAMBAH DAN KEUNTUNGAN PENGOLAHAN PRODUK KEDELAI DI UD TIGA BERSAUDARA DI KELURAHAN TAAS KECAMATAN TIKALA - Dicky Ocniel Aji Samuna; Nordy Fritsgerald Lucky Waney; Agnes Estephina Loho (Sam Ratulangi University, 2020)
The purpose of this study is to find out how much added value and benefits are, and to compare the added value of three soybean processing products at UD Tiga Brothers into tofu, sugar tofu andsoy milk. This research lasted for 3 months, from April until June 2019. Data used in this study are primary and secondary data. Primary data were obtained from direct interviews from the UD TigaBrothers factory owner, observations and records. The analysis used in this research is to use value added analysis, profit analysis, and compare the added value of the three soybean processingproducts.The results of this study indicated that the added value of processing soybeans into Chinese tofu is Rp. 37,749 / kg, the added value of processing soybeans into soy milk is Rp. 31,468 / kg and theadded value of processing soybeans into tofu sugar is Rp. 40,942.- / kg. while the benefits of processing soybeans into Chinese tofu amounted to Rp. 377,991 / kg, the profit from processing soybeans to soymilk is Rp. 33,464,5 - / kg and the profit from processing soybeans to tofu sugar is Rp. 68,140 / kg. Therefore it can be conclude the highest added value is tofu sugar product while the highest profit ischinese tofu products.*eprm*